2010
DOI: 10.5935/1806-6690.20100014
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate uptake, xylem NO3- flux, and nitrate assimilation in cowpea exposed to salinity

Abstract: Palavras-chave -Estresse salino. Nitrogênio-efeito sobre as plantas. Vigna unguiculata. Xilema.Abstract -This work was carried out to evaluate what is the nitrate acquisition stage (nitrate uptake, xylem nitrate flux or assimilatory reduction) most influenced by the presence of NaCl in cowpea. Twelve day-old seedlings were treated with 50 mM of NaCl in nutrient solution during four days and measurements carried out under two contrasting environmental conditions: typical day (full sun) and completely cloudy day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…This result is in agreement with Ding et al (2010) who worked sorghum plants and found that higher amounts of nitrate (NO 3 -) decreased the Cl -uptake, which is considered a toxic ion, thereby increasing the resistance of plants to stress caused by excess salts. This effect is possibly due to direct competition between Cl -and NO 3 -ions for the same carrier and/or alterations in membrane integrity (Mansour and Salama, 2004;Rubinigg et al, 2005;Aragão et al, 2010).…”
Section: Nitrate Contentmentioning
confidence: 99%
“…This result is in agreement with Ding et al (2010) who worked sorghum plants and found that higher amounts of nitrate (NO 3 -) decreased the Cl -uptake, which is considered a toxic ion, thereby increasing the resistance of plants to stress caused by excess salts. This effect is possibly due to direct competition between Cl -and NO 3 -ions for the same carrier and/or alterations in membrane integrity (Mansour and Salama, 2004;Rubinigg et al, 2005;Aragão et al, 2010).…”
Section: Nitrate Contentmentioning
confidence: 99%